Opiate Pain Medication Consumption in Cigarette Smokers following Total Hip Arthroplasty - Etcheson, Jennifer I.; Gwam, Chukwuweike U.; George, Nicole E.; Walia, Naval; Jerjian, Christophe; Han, Ga-ram; Virani, Sana; Miller, Seth J.; Delanois, Ronald E. (Joints, 2018)
Purpose The purpose of the present study was to assess perception of pain and pain management in smokers versus nonsmokers who received a total hip arthroplasty (THA).Methods Patients who underwent THA from 2010 to 2016 were propensity score matched 1:1 based on race, body mass index, age, and sex. This yielded 124 smokers and 124 nonsmokers. Pain intensity was quantified using area under the curve for visual analog scale pain scores. Opioid consumption was determined using a morphine milliequivalent (mEq) conversion algorithm. An independent samples t-test and Chi-square analysis was conducted to assess continuous and categorical variables respectively.Results Smokers experienced a nonsignificantly increased pain intensity (198.1 vs. 185.7; p = 0.063). Smokers demonstrated significantly higher opioid consumption in both immediate postoperative (65.9 vs. 59.3 mEq; p = 0.045) and 90 days postoperative periods (619.9 vs. 458.9 mEq; p = 0.029).Conclusion Our study demonstrated a nonsignificantly increased pain intensity, and (in both the immediate and 90 days postoperative periods) a significantly higher opioid consumption following THA in patients who smoke cigarettes. This may be due to a relatively small effect size, warranting the need for larger prospective studies. Nevertheless, arthroplasty surgeons should encourage preoperative smoking cessation and alternative nonopioid analgesics to smoking patients receiving THA.Level of Evidence This is a level III, retrospective cohort study.
Keywords: total hip arthroplasty; narcotics; cigarette smoking; opioids; pain